1, 2, 3, MHC: a review of mass-spectrometry-based immunopeptidomics methods for relative and absolute quantification of pMHCs. (October 2021) - Stopfer, L.E.; D'Souza, A.D.; White, F.M.
Abstract : Quantitative mass-spectrometry-based methods to perform relative and absolute quantification of peptides in the immunopeptidome are growing in popularity as researchers aim to measure the dynamic nature of the peptide major histocompatibility complex repertoire and make copies-per-cell estimations of target antigens of interest. Multiple methods to carry out these experiments have been reported, each with unique advantages and limitations. This article describes existing methods and recent applications, offering guidance for improving quantitative accuracy and selecting an appropriate experimental set-up to maximize data quality and quantity. Highlights: Existing methods for quantitative immunopeptidomic analysis are described. Guidance to improve quantitative accuracy is offered. Experimental design guidance is provided to maximize data quality and quantity.